Atypically Protracted Course of Liver Involvement in Kawasaki Disease. Case Report and Literature Review - Pamela Paglia; Lucia Nazzaro; Anna Giulia Elena De Anseris; Milena Lettieri; Rossella Colantuono; Maria Chiara Rocco; Maria Anna Siano; Nicola Biffaro; Pietro VAJRO (MDPI AG, 2021)
Hypertransaminasemia in patients with Kawasaki disease (KD) is reported to be transient. Here, we describe a child with an atypically protracted course of liver tests abnormalities and review the inherent literature. The patient was hospitalized at age 7-months for isolated hypertransaminasemia detected during a classical KD diagnosed 3 months before, and persistent since then. KD clinical evolution had been favorable, with rapid response to acetylsalicylic acid and intravenous immunoglobulins. Liver enzymes however remained persistently elevated with a fluctuating pattern (ALT > AST levels; peak of AST 186 IU/L and ALT 240 IU/L). During follow-up, the main causes of liver dysfunction had to be excluded through appropriate and extensive laboratory investigations. Transaminases values become steadily normal only 7 months after the acute presentation of KD. Conclusions: Our report shows that an atypically protracted courses of KD-related hypertransaminasemia above the previously reported temporal limits should be taken into account during the stepwise diagnostic approach to the patient's liver dysfunction. Insidious acetylsalycilic acid-hepatotoxicity warrants consideration in the differential diagnosis.